2020
DOI: 10.3390/jcm9041076
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factor Possession Patterns of Dementia in Elderly with MCI: A 4-Year Repeated Measures Study

Abstract: This study clarified the patterns of possessing modifiable risk factors of dementia that can be corrected by the elderly who were primarily determined to have mild cognitive impairment (MCI), and then determined the relationship between retention patterns and outcomes from MCI through a 4-year follow-up study. The participants were 789 community-dwelling elders who were ≥65 years old with MCI at baseline. After 4 years, participants were classified into reverters and nonreverters, according to their cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In addition, we found that rMCI was more likely to occur in non-smoking individuals in the ADNI sample (Additional file 1 : Table S3). Two other recent studies have reached the same conclusion that non-smoking is a beneficial factor in reversing from MCI to NC state [ 58 , 59 ]. However, another study found no differences in vascular risk factors between the MCI reversion, stabilization, and progression groups, with low white matter hyperintensity grades characteristic of MCI reversion [ 60 ].…”
Section: Discussionmentioning
confidence: 53%
“…In addition, we found that rMCI was more likely to occur in non-smoking individuals in the ADNI sample (Additional file 1 : Table S3). Two other recent studies have reached the same conclusion that non-smoking is a beneficial factor in reversing from MCI to NC state [ 58 , 59 ]. However, another study found no differences in vascular risk factors between the MCI reversion, stabilization, and progression groups, with low white matter hyperintensity grades characteristic of MCI reversion [ 60 ].…”
Section: Discussionmentioning
confidence: 53%
“…There is currently no consensus on the best approach to operationalize and synthesize MDRFs. Several methods have been used previously such as considering MDRFs individually (Jonaitis et al, 2013), weighted risk scores (e.g., CAIDE; Kivipelto et al, 2006), and data-driven approaches (Katayama et al, 2020). Methods other This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, reversion is also more likely in younger patients, 12–15 as well as in those with better scores on general cognitive assessments and with higher amygdala and hippocampus volumes, 16,17 with better vision and olfactory ability, and with higher scores on the personality trait of openness to experience 17 . Other modifiable variables such as smoking, obesity, and hypertension are also associated with cognitive impairment and dementia and their progression 18 …”
Section: Introductionmentioning
confidence: 99%
“…17 Other modifiable variables such as smoking, obesity, and hypertension are also associated with cognitive impairment and dementia and their progression. 18 Regarding neuropsychiatric symptoms, patients with fewer mixed anxious-depressive symptoms seem to revert more easily than those with higher scores in anxiety, apathy, or depression. 15,19 Paradoxically, affective symptoms have also been found to be a predictor for reversion.…”
mentioning
confidence: 99%